2015
DOI: 10.1039/c5sm00473j
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the mesomorphic properties of phenoxy-terminated smectic liquid crystals: the effect of fluoro substitution

Abstract: The mesomorphic properties of phenoxy-terminated 5-alkoxy-2-(4-alkoxyphenyl)pyrimidine liquid crystals can be tuned in a predictable fashion with fluoro substituents on the phenoxy end-group. We show that an ortho-fluoro substituent promotes the formation of a tilted smectic C (SmC) phase whereas a para-fluoro substituent promotes the formation of an orthogonal smectic A (SmA) phase. The balance between SmA and SmC phases may be understood in terms of the energetic preference of the phenoxy end-groups to self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…Phenoxy end-groups have been reported to suppress SmC phases, 19 and the positions of fluorine substituents on phenoxy end-groups have been shown to influence the relative stabilities of the SmA and SmC phases. 20 In some cases, bulky non-polar end-groups have been proposed to preclude liquid-crystalline phases 16 and weaken interlayer interactions 21 due to their volume, but other studies have suggested that such groups may increase the temperature range over which the SmA phase is stable, 18 or enhance the stability of the SmC phase over the SmA phase. 22 It has also been reported that SmC stabilisation by bulky non-polar groups may only occur if the bulky group is not too large.…”
Section: Introductionmentioning
confidence: 99%
“…Phenoxy end-groups have been reported to suppress SmC phases, 19 and the positions of fluorine substituents on phenoxy end-groups have been shown to influence the relative stabilities of the SmA and SmC phases. 20 In some cases, bulky non-polar end-groups have been proposed to preclude liquid-crystalline phases 16 and weaken interlayer interactions 21 due to their volume, but other studies have suggested that such groups may increase the temperature range over which the SmA phase is stable, 18 or enhance the stability of the SmC phase over the SmA phase. 22 It has also been reported that SmC stabilisation by bulky non-polar groups may only occur if the bulky group is not too large.…”
Section: Introductionmentioning
confidence: 99%
“…By adding an additional aromatic group at the end of the molecule, attractive noncovalent π‐π interactions between these aromatic groups can improve the nanosegregation. Stronger nanosegregation enhances the stability of smectic phases, and it also stabilizes the SmC phase as stronger nanosegregation reduces the out‐of‐layer fluctuations, and this minimizes the entropic cost of molecular tilt in a smectic structure . The aromatic imidazolium head groups can form π + ‐π + interactions between the positively charged aromatic rings .…”
Section: Resultsmentioning
confidence: 54%
“…There are relatively few examples of ILCs with SmC phases described in the literature, most notably calamitic biphenyls, phenylpyrimidines, and azobenzenes with various cationic head groups. However, general design principles for SmC promoting mesogens are unknown for ILCs in contrast to the guidelines successfully developed by Lemieux for noncharged liquid crystals . From our previous findings that alkoxybiphenyls with tethered guanidinium moiety displayed indeed SmC phases in addition to the SmA phase, when the spacer was sufficiently long, we concluded that the connection of the cationic head group with a rigid calamitic unit via a flexible tether seems to be a promising design motive for that purpose.…”
Section: Introductionmentioning
confidence: 99%
“…LC dimers may be divided into two broad classes: symmetric [10,37,42] and nonsymmetric. [21,23,24,[29][30][31][32][33][34][35]42,43] In a symmetric LC dimer, the two mesogenic units are identical, whereas they are different in a non-symmetric dimer. The intercalated smectic phase was first observed in the study of LC dimers and, specifically, in non-symmetric dimers.…”
Section: Introductionmentioning
confidence: 97%
“…), mesophase morphology and transition temperatures. [1,5,[20][21][22][23] The simultaneous introduction of chirality and fluoro substituent into the LC molecule leads to new chiral functional materials. [5,19,24] It is necessary to synthesise different types of chiral fluorinated LCs to gain a better understanding of the factors controlling their properties.…”
Section: Introductionmentioning
confidence: 99%